Differential Gene Expression of Cardiac Ion Channels in Human Dilated Cardiomyopathy - Maria Micaela Molina‐Navarro; Esther Roselló‐Lletí; Ana Ortega; Estefanía Tarazón; Manuel Otero; Luis Martínez‐Dolz; Francisca Lago; José Ramón González‐Juanatey; Francisco España; Pablo García‐Pavía; José Montero; Manuel Portolés; et al. (2013)
BackgroundDilated cardiomyopathy (DCM) is characterized by idiopathic dilation and systolic contractile dysfunction of the cardiac chambers. The present work aimed to study the alterations in gene expression of ion channels involved in cardiomyocyte function. Methods and ResultsMicroarray profiling using the Affymetrix Human Gene® 1.0 ST array was performed using 17 RNA samples, 12 from DCM patients undergoing cardiac transplantation and 5 control donors (CNT). The analysis focused on 7 cardiac ion channel genes, since this category has not been previously studied in human DCM. SCN2B was upregulated, while KCNJ5, KCNJ8, CLIC2, CLCN3, CACNB2, and CACNA1C were downregulated. The RT-qPCR (21 DCM and 8 CNT samples) validated the gene expression of SCN2B (p < 0.0001), KCNJ5 (p < 0.05), KCNJ8 (p < 0.05), CLIC2 (p < 0.05), and CACNB2 (p < 0.05). Furthermore, we performed an IPA analysis and we found a functional relationship between the different ion channels studied in this work. ConclusionThis study shows a differential expression of ion channel genes involved in cardiac contraction in DCM that might partly underlie the changes in left ventricular function observed in these patients. These results could be the basis for new genetic therapeutic approaches.